Confirmation of recent heroin abuse: Accepting the challenge. Issue 1 (5th September 2017) - Maas, Alexandra; Madea, Burkhard; Hess, Cornelius
Abstract: Confirmation or exclusion of recent heroin consumption is still one of the major challenges for forensic and clinical toxicologists. A great variety of biomarkers is available for heroin abuse confirmation, including various opium alkaloids (eg, morphine, codeine), street heroin impurities (eg, 6‐acetylcodeine [6‐AC], noscapine, papaverine) as well as associated metabolites (eg, 6‐monoacetylmorphine [6‐MAM], morphine glucuronides). However, the presence of most of these biomarkers cannot solely be attributed to a previous heroin administration but can, among other things, also be due to consumption of poppy seed products ('poppy seed defense'), opium preparations or specific medications, respectively. A reliable allocation is of great importance in different contexts, for instance in the case of DUID (driving under the influence of drugs) investigations, in driving licence re‐granting processes, in workplace drug testing (WDT), as well as in post‐mortem identification of illicit opiate use. Additionally, differentiation between illicit street heroin abuse and pharmaceutical heroin administration is also important, especially within the frame of heroin‐assisted treatments. Therefore, analysis of multiple biomarkers is recommended when illicit opiate consumption is assumed to obtain the most reliable results possible. Beyond that, interpretation of positive opiate test results requires a profound insight into the great variety of biomarkers available and their validity regarding the alleged consumption. This paper aims to provide an overview of the wide variety of heroin abuse biomarkers described in the literature and to review them regarding their utility and reliability in daily routine analysis. Abstract : Confirmation or exclusion of recent heroin consumption is still one of the major challenges for forensic and clinical toxicologists. A great variety of biomarkers is available for heroin abuse confirmation, including various opium alkaloids, street heroin impurities, as well as associated metabolites. This paper aims to provide an overview of the wide variety of heroin abuse biomarkers described in the literature and to review them regarding their utility and reliability in daily routine analysis.